From a Fishermen’s Village to a Resort: Relationship between Holidaymakers and Hosts in the Texts of the Residents of the Curonian Spit - Kiseliūnaitė, Dalia (Acta humanitarica academiae Saulensis, 2023)
The article aims to reveal the attitude characteristic of the residents of the Curonian Spit towards interwar-time (1923–1939) holidaymakers whom they provided with hospitality services. Regarding the ethnocultural space of the Curonian Spit, it is usual to refer to the published impressions from the 19th and the first half of the 20th century. Despite the political accents and different interpretations, the impressions are conveyed through the eyes of holidaymakers or short-term guests. So far, little attention has been paid to the social self-awareness of the local population amid significant political and social changes in the region. This interdisciplinary research is based on linguistic and ethnographic material. In the narratives based on the subjective experience of the residents, the regional concepts of “recreation”, “holidaymaker”, “one’s own/stranger”, “hospitality”, content and linguistic expression come to light. Texts and their fragments reflecting the topic were selected from the linguistic and ethnographic material collected in the field research between 1980 and 2004 and analyzed using the methods of text and, partially, concept analysis.